Relationship Between Knowledge and Utilization of Adolescent Care Health Services in Padang City - Melisa Yenti; Arinil Haq; Shelvy Haria Roza; Mivtahurrahimah Mivtahurrahimah (Jurnal Kesehatan Masyarakat Andalas, 2022)
The transition of children to adulthood through adolescence tends to be more daring to take risks so that it has an impact on reproductive health problems such as promiscuity leading to premarital sex, abortion, and the emergence of HIV-AIDS. So far, the government has carried out prevention through the Youth Care Health Service (PKPR) and has been implemented throughout Indonesia, including the city of Padang. However, the scope of services provided is still low. This study was conducted to examine the knowledge of high school students in the use of PKPR in Padang City in 2020. It was carried out through a cross-sectional approach at Padang City High School in March – October 2020. 145 students were analyzed using the Mann-Whitney test. The results showed that there was a significant average difference between knowledge on the use of PKPR. For the use of PKPR to be increased and maximized, and educational promotion program is needed about the use of PKPR for adolescents by stakeholders and the government considering that knowledge and utilization of PKPR by adolescents is still low.